Back Cover: Advanced Engineering Materials 9∕2015. Issue 9 (September 2015) - Unknown
<x xml:space="preserve">Abstract</x> The fabricated titanium matrix composites (TMCs) with 2.5 (TMC 2.5) and 7.5 vol.% (TMC 7.5) in situ TiC contents have invariable plasticity and ultimate compression stress. This can be explained by establishing a relationship between serrated flow behavior of stress‐strain curves and shear‐band interactions during plastic deformation in the TMCs. Further details can be found in the article by C. Yang and co‐worker on page 1383.